Job demands-resources, job crafting and work engagement of tobacco retailers - Daokui Jiang; Lei Ning; Teng Liu; Yiting Zhang; Qian Liu (Frontiers Media S.A., 2022)
In recent years, the development of tobacco control actions in China and the changes in people's health concepts have slowed the development of the tobacco industry. As an important strategic partner of tobacco sales companies, tobacco retailers are the key link between tobacco commercial enterprises and consumers. How to improve the work engagement level of tobacco retailers is an urgent issue for tobacco business enterprises. On the basis of job demands-resources (JD-R) theory, the mechanisms of the effects of job resources and demands on tobacco retailers' work engagement were explored. Results showed that (1) The negative path of job demands influencing tobacco retailers' work engagement was supported, and job crafting played a mediating role in it. (2) The positive path of job resources influencing tobacco retailers' work engagement was supported, and job crafting played a mediating role in it. (3) Servant leadership moderated the influence of job resources and demands on job crafting. Higher level of servant leadership brings the stronger effect of job resources on job crafting and the weaker effect of job demands on job crafting. (4) The mediating effect of job crafting between JD-R and work engagement was moderated by servant leadership. The higher level of servant leadership strengthened the mediating role of job crafting between job demands and work engagement, whereas it weakened the mediating role of job crafting between job demands and work engagement. This study enriches the research on application fields and boundary conditions of JD-R theory and provides practical guidance for improving the work engagement level of tobacco retailers.